Frequency analysis of changes and disease symptoms in wild boars in Poland in 2015-2019 - Górski, Krzysztof; Bombik, Elżbieta; Kondracki, Stanisław (2021)
The aim of the study was to analyse the results of the post-mortem sanitary and veterinary examinations of wild boar by the Veterinary Inspection in Poland between 2015 and 2019. The examination took into account changes such as emaciation, septicaemia and pyaemia, parasitic diseases and other. Analyses determined the number of animals examined, the number of carcasses with lesions, and the number of carcasses declared unfit for consumption. During the study period, more than 680,000 wild boars were subjected to sanitary and veterinary tests in Poland. Symptoms or lesions were found in 11,566 animals (1.70%), and 10,883 (1.60%) animals were declared unfit for consumption. The percentage of wild boar carcasses with lesions examined by year ranged from 1.23% in 2015 to 2.02% in 2019 and the percentage of wild boar carcasses declared unfit in relation to all carcasses tested ranged from 1.23% in 2015 to 1.88% in 2019. Parasitic lesions were found in 3488 wild boar carcasses, accounting for 30.16% of all changes recorded in wild boar carcasses. The most common parasitic disease was trichinellosis and the most frequent change was emaciation, which was recorded in 2665 (0.39%) animals. Putrefaction is a common lesion in wild boar carcasses, and was detected in 2546 (0.37%) animals. Territorial differences were found in the frequency of lesions in wild boars in Poland. The most trichinellosis cases in carcasses was recorded in Zachodniopomorskie Voivodeship (748) and Wielkopolskie Voivodeship (638). Kujawsko-pomorskie Voivodeship and Wielkopolskie Voivodeship together had a total of 2324 cases of emaciation, accounting for 87.2% of all cases of these changes registered in the study period.
Cilj studije bio je analizirati rezultate obdukcijskog pregleda divljih svinja u Poljskoj između 2015. i 2019. godine. Analizirani su rezultati službenog sanitarnog i veterinarskog pregleda divljih svinja kojeg je obavila Veterinarska inspekcija. Procjena je uzela u obzir promjene poput mršavljenje, septikemije i pijemije, parazitskih bolesti i druge promjene. Analiza rezultata testa uzela je u obzir broj ispitanih životinja, broj leševa na kojima su otkrivene lezije i broj leševa proglašenih neprikladnima za konzumaciju. Više od 680 tisuća divljih svinja podvrgnuto je sanitarnim i veterinarskim testovima u Poljskoj između 2015. i 2019. godine. Tijekom studije otkriveni su simptomi ili lezije u 11566 životinja, što čini 1,70 %. 10883 životinja proglašeno je neprikladnima za konzumaciju. To je predstavljalo 1,60 % svih ispitanih životinja. U pojedinačnim godinama, postotak leševa divljih svinja na kojima su otkrivene lezije kretao se od 1,23 % 2015. godine do 2,02 % 2019. Postotak leševa divljih svinja proglašen neprikladnim za konzumaciju u odnosu na sve ispitane leševe kretao se od 1,23 % 2015. godine do 1,88 % 2019. Parazitske lezije otkrivene su na 3488 leševa divljih svinja. One su predstavljale 30,16 % svih promjena zabilježenih na leševima divljih svinja. Najčešća parazitska bolest otkrivena u divljih svinja bila je trihineloza. Najčešća promjena u leševa divljih svinja bilo je mršavljenje. Ova promjena otkrivena je u razdoblju 2015.-2019. godine u 2665 divljih svinja (0,39 %). Trulež je česta lezija u leševa divljih svinja. Takve promjene otkrivene su u razdoblju 2015.-2019. godine u 2546 divljih svinja (0,37 %). Učestalost lezija u divljih svinja u Poljskoj pokazuje teritorijalne razlike. Između 2015. i 2019. godine najveći broj slučajeva trihineloze u leševa divljih svinja zabilježen je u Zachodniopomorskie vojvodstvu (748) i Wielkopolskie vojvodstvu (638).
Bibliografija: 30 jed.
Abstract ; Sažetak.
Keywords: Divljač -- Divlja svinja -- Sanitarna inspekcija -- Veterinarska inspekcija -- Lezije